Influence of experimental cremation in conditions close to those in praehistory on the morphology of bones - Strzałko, Jan; Piontek, Janusz (Anthropological Review, 1974)
The authors purpose was explanation whether changes of shape and size of bones observed in the course of cremations in gas-hcated modern crematory resemble such a changes in bones cremated on the wooden stake. In this order was carried out some experimental cremations of human bones on stakes arranged in various manners. There was also burned monkey’s corpse in order to evaluate the influence of soft tissues on bones cremation. Microscopical and macroscopical changes of size and shape of bones under influence of high temperature observed during the cremations in gas-stoves, and described in literature are taking place also in the case of cremations on wooden stake. These changes, as have been shown experimentally do not depend on presence or absence of soft tissues and are of two sorts: 1. in the bone are burned out organic components, 2. there are changes of inorganic components. Good evidence of this results were observations made during the cremation of mokey’s corpse. Our observations suggest that, when bones are burned in proper temperature. mode and range of changes in their size and shape do not depend on the manner of cremation. Temperature of burning stake, as we could see from changes in metrical characters of long bones (tab. 1), skull (tab. 2) and tooth morphology, in high enough for distortion and contraction of bones. The authors have also shown, that some characters of skeletal material, and some fragments of bones do not underwent changes during the cremation. They are first of all the relief of the muscle attachement and degree of expression such skull characters as: upper rim of orbita, mastoid process superciliary arch, e.t.c. and degree of involutionary changes on the symphyseal surface of os pubis. Multidirectional character of changes in size and shape during the cremation makes very difficult or even impossible attempts to reconstructions the physical characters of individuals. Taking into account degree of contraction of bones during the cremation we are able to reconstruct satisfactorily the lenght of bones their proportions and stature. Reconstruction of metrical characters of skull has a great range of error. This error has significant influence on the morphological, comparative analysis.